The Influence of Capital Structure, Profitability, and Company Growth on Company Value - ludwiga, Sevira Adellia; Dewi, Anita Kusuma; Nurmala, Nurmala (Penerbit Goodwood, 2025)
Purpose: The purpose of this study is to examine the effect of capital structure, profitability, and company growth on firm value in transportation and logistics companies listed on the Indonesia Stock Exchange for the period 2020–2024. Methodology/Approach: This study was conducted using a quantitative approach. The data was collected from the financial reports of transportation and logistics companies listed on the Indonesia Stock Exchange. The analysis was carried out using Microsoft Excel and SPSS 27 software. The method used for testing was multiple linear regression analysis. Results/Findings: The results showed that capital structure and profitability had a significant positive effect on firm value, while company growth did not have a significant effect on firm value. Conclusions: It can be concluded that firm value in transportation and logistics companies is more influenced by how efficiently they manage capital and generate profits than by growth opportunities. Limitations: This study is limited to secondary data from financial statements and does not consider qualitative factors or macroeconomic variables that may influence firm value. Contribution: This research contributes to the field of financial management, especially in helping investors and company management understand which internal financial factors most influence firm value in the transportation and logistics sector in Indonesia.